Legal consequences of bush burning and forest fires in Oyo, Osun, Ogun and Ondo States: The criminal and civil consequences (1996)
This paper examines existing Laws, By-Laws and Regulations guiding bush burning and forest fires in Oyo, Osun , Ogun , and Ondo States of Nigeria and highlights the legal consequences from the criminal and civil perspectives of breaching the law . Every year, properties worth millions of Naira are destroyed in these states as a result of fire incident caused by farmers , hunters and nomads who use fire for land clearing , killing of animals or growth of foliage for animals respectively. Bush burning has been particularly recognized as a precarious agent of accidental fire outbreaks. Though bush burning is an acceptable customary practice , effort should be made to introduce new improved and more productive methods of farm clearing and hunting methods to people in these States